Examining the effects of Project-Based Learning on EFL learners’ reading achievement: The role of learner self-regulation - Selamet Riadi Jaelani; Nunung Suryati; Yazid Basthomi; Nurenzia Yannuar; Dian Resty Pratiwi Ahmad; Endah Ratnaningsih (Universitas Syiah Kuala, 2026)
This study examined how Project-Based Learning (PJBL) and Problem-Based Learning (PBL) affect EFL learners’ reading, with a particular emphasis on interactions with learners’ characters (high and low). The study employed a quasi-experimental design with 64 senior high school students from two classes. The students were divided into experimental and control groups. The data was collected using a 60-item reading comprehension test. The results were analyzed statistically, including Tukey’s HSD test, to examine significance and interaction effects. PJBL relies heavily on self-motivation and discipline; the results indicated a statistically significant mean difference of -14.56 (p < 0.05) between students with low character and those with high character. This suggests that PJBL was not effective for low-character learners, especially those who struggle with self-regulation. Low-character students in PJBL scored significantly lower than high-character students in PBL, with a mean difference of -7.66 (p < 0.05). In contrast, high-character students in PJBL performed significantly better than low-character students in PBL, with a mean difference of 11.91 (p < 0.05). They also outperformed high-character students in PBL, with a mean difference of 6.91 (p < 0.05). Therefore, PJBL is more effective for high-character learners because it requires independence. However, there was no significant distinction between PJBL and PBL for low-character learners (mean = 2.66, p > 0.05), indicating that these students require additional support in all educational settings. To maximize reading outcomes in the EFL context, our findings emphasize the importance of aligning instructional strategies with learner characteristics.